(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda, a divine science of life, transferred from immortals to mortals for the welfare of mankind. It precisely emphasize on maintenance of health, for this purpose it describes the use Nitya sevaniya dravyas and Rasayana dravyas accordingly. Among them, milk is considered as best and is compared with nectar. But now a day, many people are diagnosed as lactose intolerant, where as in Ayurvedic texts ‘Satmya’ is mentioned as Guna of Dugdha. In the text Sushen Nighantu we find a term ‘Dudgha asatmya’ which seems similar to lactose intolerance, the symptom Adhmana is referred to it. Also in text like Ajirna Manjari and Kshemakutuhalam we find treatment for Ksheerapanajanya ajirna. But any symptoms are not told. This disease comes under the umbrella of Anukta vyadhi. Acharya Charaka has given guidelines to treat Anukta vyadhi. An effort to understand lactose intolerance in Ayurvedic point of view will be made here. A literary study to find references, probable co-relation and comparison of Ksheera pana janya ajirna and lactose intolerance will be done in this article.